An evaluation of the latest evidence relating to renin–angiotensin system inhibitors. (July 2013) - Escobar, Carlos; Barrios, Vivencio
<x xml:space="preserve">Abstract</x> Introduction: In the last few years, a number of important clinical trials have been completed that have investigated the inhibition of the renin–angiotensin system. New drugs, focusing on this system, have now emerged as a result. Areas covered: The authors review the most relevant information available, reported from the last 5 years, pertaining to the most important clinical trials on renin–angiotensin system blockers (ARBs). The authors' data review includes the trials of aliskiren, telmisartan, olmesartan and azilsartan. The authors also review the possible risk of cancer with ARBs. Expert opinion: The results of ASPIRE and ALTITUDE trials strongly suggested that dual inhibition of aliskiren with either ARBS or angiotensin converting enzyme inhibitors (ACEi) should be avoided. Olmesartan is an effective and safe antihypertensive agent, but special attention should be paid to high-risk patients, such as those with coronary disease, to avoid an excessive reduction in blood pressure. The authors also note that while azilsartan is probably the most potent ARB, there is still a lack of data regarding potential organ damage and the incidence of cardiovascular events. Lastly, recent evidence has shown a lack of a relationship between ARB therapy and the occurrence of cancer.